The Modus Operandi Of Illegal Breaking And Entering Landed Houses In Penang - Ahghar, Narges (2018)
This study examines the effect of the physical characteristics of landed house on breaking and entering and modus operandi of breaking and entering on Penang Island. In addition to previous research studies, the recorded burglary databases of Penang State by the Department of Police in 2009 was used to indicate items that explain modus operandi and identify effective exterior physical factors of houses on burglary and modus operandi of breaking and entering. Findings of this quantitative study are based on the responses obtained from a survey of 300 households in a high burglary crime area in Penang Island.